Genomic Epidemiology Analysis of Infectious Disease Outbreaks Using TransPhylo. Issue 2 (22nd February 2021) - Didelot, Xavier; Kendall, Michelle; Xu, Yuanwei; White, Peter J.; McCarthy, Noel
Abstract: Comparing the pathogen genomes from several cases of an infectious disease has the potential to help us understand and control outbreaks. Many methods exist to reconstruct a phylogeny from such genomes, which represents how the genomes are related to one another. However, such a phylogeny is not directly informative about transmission events between individuals. TransPhylo is a software tool implemented as an R package designed to bridge the gap between pathogen phylogenies and transmission trees. TransPhylo is based on a combined model of transmission between hosts and pathogen evolution within each host. It can simulate both phylogenies and transmission trees jointly under this combined model. TransPhylo can also reconstruct a transmission tree based on a dated phylogeny, by exploring the space of transmission trees compatible with the phylogeny. A transmission tree can be represented as a coloring of a phylogeny where each color represents a different host of the pathogen, and TransPhylo provides convenient ways to plot these colorings and explore the results. This article presents the basic protocols that can be used to make the most of TransPhylo. © 2021 The Authors. Basic Protocol 1 : First steps with TransPhylo Basic Protocol 2 : Simulation of outbreak data Basic Protocol 3 : Inference of transmission Basic Protocol 4 : Exploring the results of inference